Vegetation Structure and Carbon Stock of Two Community Managed Shorea robusta Forests of Dhangadhi, Nepal - Joshi, Gyanu; Sharma, Krishna Prasad; Chettri, Mukesh Kumar (Amrit Research Journal, 2021)
Community forests play a vital role in sustainable development and storing carbon stock to mitigate global warming. This study aimed to assess the plant diversity, carbon stock and regeneration status of two Shorea robusta forests managed by the community - Manehara Community Forest (MCF) and Siddhanath community forests (SCF) of Kailali district, Nepal. These two forests differ in the moisture regime- MCF is with ponds and streams and is mostly wet, but SCF is primarily dry with no ponds and streams. To examine vegetation status and carbon stock in these two forests, twenty circular plots of 20 m radius was laid in each forest using stratified random sampling. Within each main plot, two subplots of 5m radius and three subplots of 2m radius were laid to study shrub and herb characteristics, respectively. Soil sampling was also done to analyze the role of soil moisture in carbon stock and regeneration. For this, soil samples of each plot were collected up to 20cm depth. Altogether 100 plant species were recorded from the study forests. Tree and shrub diversity was higher in MCF than in SCF, but herb diversity and seedling numbers were higher in relatively dry SCF than in MCF. The carbon stock of MCF (92.99t/ha) was higher than in SCF (51.94 t/ha). In both forests, carbon stock increased with the increasing basal area (P = 0.0001). A significant strong positive relationship (P = 0.0001) between density and carbon stock was found in SCF, but this relation was weak (P = 0.018) in MCF. Both community forests were fairly regenerating with a good number of small aged individuals, SCF shows an inverted J shaped density diameter (d-d) curve, whereas MCF shows a bell-shaped d-d curve.